Risk and Protective Factors Associated with Youth Firearm Access, Possession or Carrying - Mattson, Sabrina Arredondo (American journal of criminal justice, 2020)
Firearm homicide and suicide are the leading causes of violence-related injury deaths among U.S. youth. However, evaluations of the effectiveness of firearm violence prevention programs and strategies to reducing youth firearm violence are limited. To help inform and evaluate such efforts, this study aimed to identify risk and protective factors associated with youth firearm access, possession or carrying (for reasons other than hunting or target shooting) among a sample of U.S. urban youth in the Mountain West. Findings show the influence that youth violence risk (e.g., having friends engaged in delinquency; violence; drug sales; gang fights; exposure to violence; screening positive for violence risk) can have on youth firearm access, possession or carrying. Implications for prevention and intervention are discussed.